2021
DOI: 10.1177/00178969211045722
|View full text |Cite
|
Sign up to set email alerts
|

Does food and health education in school influence students’ everyday life?

Abstract: Objective: The Norwegian National Action Plan for a Healthier Diet calls for discussion of new ways to communicate health information. An already established and important arena in which to do so is school, in the Food and Health (FH) subject in particular. The aim of this study was to investigate how Norwegian students experience the FH subject, and how they believe it impacts on their everyday lives. Design: Qualitative study using focus group discussions Setting: Three public schools in Norway Methods: Focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
1
8
0
2
Order By: Relevance
“…And as such, FH could increase in importance for pupils' learning and future lives, thus harnessing the FH subjects' potential. We, unfortunately, know little about the impact of FH specifically on pupils and their lives per se (Beinert et al, 2022), but we argue that it is plausible it may have an impact with more systematic food education in the short, medium and long term. Is it worth gambling with our future generations?…”
Section: Overall Discussion and Conclusionmentioning
confidence: 84%
“…And as such, FH could increase in importance for pupils' learning and future lives, thus harnessing the FH subjects' potential. We, unfortunately, know little about the impact of FH specifically on pupils and their lives per se (Beinert et al, 2022), but we argue that it is plausible it may have an impact with more systematic food education in the short, medium and long term. Is it worth gambling with our future generations?…”
Section: Overall Discussion and Conclusionmentioning
confidence: 84%
“…[3] A study in Norway found that food and health education have relevance to students' daily life, but have little to no effect on healthy food choices among 31 7th to 10th grade students. [11] This study claims to strengthen teachers' competence on food choices. Additionally, fully 100% of Taiwan nursing students study health education in Community Health Nursing course before taking national registered nurse examination.…”
Section: Current Status Of Healthy Diet Knowledgementioning
confidence: 98%
“…A healthy diet is fundamental to a correct nutritional education because habits established at this early stage are difficult to change in adulthood" (Menor-Rodriguez et al, 2022). The study by Beinert et al (2022), states ISSN: 2661-6831 Vol. 7 No.…”
Section: Category 4: Barmentioning
confidence: 99%